An aspect of residential distribution pattern in Kuala Lumpur: an observation - Abdul Samad Hadi (Universiti Kebangsaan Malaysia, 1975)
The paper describes the distribution of high status residential area of Kuala Lumpur using the 1971 Malaysia's Who's Who as a source for data. Although the Who's Who does not form a complete source of information, in the absence of published data the Who's Who does give an indication of high status residential area distribution in Kuala Lumpur. Results indicate that the high status areas show a widespread distribution over Kuala Lumpur - Petaling Jaya with major concentrations on Kenny Hill, Ampang area, Damansara - Lake Garden area and the Circular - Golf Link Road area of Kuala Lumpur while in Petaling Jaya several concentrations are seen in many parts of the town with a major focus in section 16.